Siblings - friends or foes? - Pike, Alison; Kretschmer, Tina; Dunn, Judith F. (Psychologist, 2009)
The vast majority of us have at least one brother or sister, yet sibling relationships have received scant attention in the UK. While many parents claim to have a second child as a 'companion' for their first child, the reality is that many brothers and sisters spend much of their time locked in conflict. At the extreme, it is in fact the case that children are more likely to become the victims of abuse by a sibling than by any other family member. On the flip side, many brothers and sisters are, at least at times, the best of friends. This article describes a study designed to uncover features of families as well as individual children that foster warm, intimate relationships between siblings versus hostile, conflict-ridden brother-sister interactions.
CRIS-Team Scopus Importer:2025-03-19